Correlation Between Prostate-Specific Antigen Density and Findings from Multiparametric Magnetic Resonance Imaging of Prostate - Öztürk, Cansu; Güngör, Özlem; Ersay, Hanife; Uysal Ramadan, Selma (Cerrahpaşa Medical Journal, 2022)
Objective: The present study is intended to investigate the relationship between multiparametric prostate magnetic resonance findings and prostatespecific antigen density in the diagnosis of prostate cancer. Methods: The present study included 38 cases that underwent multiparametric prostate magnetic resonance between January 1, 2019, and February 28, 2022. Age, prostate-specific antigen, transrectal ultrasound biopsy, prostate-specific antigen density, and prostate imaging-reporting and data system results of all cases were recorded. Together with the prostate-specific antigen density threshold value, the sensitivity and specificity of prostate-specific antigen density and prostate imaging-reporting and data system scores in predicting histopathological outcomes were calculated. Results: Of the patients undergoing transrectal ultrasound biopsy, 11 patients (28.9%) were diagnosed with prostate cancer. The median prostatespecific antigen density was higher in the group of malignant cases [0.2 (0.1-1.9) ng/mL2] than in the group of non-malignant cases [0.1 (0.03- 0.57) ng/mL2] (P < .0001). With the prostate-specific antigen density threshold value set at 0.16 ng/mL2, the sensitivity was 73% and the specificity was 89% in predicting prostate cancer, while positive predictive value was 73% and negative predictive value was 89% (area under the curve: 0.864, P < .001). Multiparametric prostate magnetic resonance findings had a sensitivity of 91% and a specificity of 85%, as well as positive predictive value of 71% and negative predictive value of 96% in predicting prostate cancer (P < .001). There was a strong correlation with the biopsy result in the prostate imaging-reporting and data syste m/pro state -spec ific antigen density positive group (Rho: 0.79, P < .0001) where the sensitivity, specificity, and negative predictive value were found to be 100%, 78%, and 100%, respectively. Conclusion: The results of the present study demonstrated that the combined use of prostate-specific antigen density and multiparametric prostate magnetic resonance imaging helps obtain more robust results in diagnosing prostate cancer, compared to using either of them individually. Cite this article as: Öztürk C, Güngör Ö, Ersay H, Uysal Ramadan S. Correlation between prostate-specific antigen density and findings from multiparametric magnetic resonance imaging of prostate. Cerrahpaşa Med J. October 4, 2022. 2022;46(3):189-193.